Acute toxicity bioassay of copper on juveniles and adults of the freshwater catfish, Mystus vittatus (Bloch.) - Subathra, S; Karuppasamy, R; Sivakumar, S (Indian Journal of Fisheries, 2011)
An attempt was made to assess the acute toxicity of copper against juveniles and adults of the freshwater fish, Mystus vittatus. The static, renewable bioassay method was adopted to determine the lethal concentration (LC50) through probit analysis. The values of 24, 48, 72 and 96 h LC50 for juveniles were 38.90, 28.84, 25.11 and 18.62 mg/l respectively and those of adult fish were 89.13, 69.18, 56.23 and 47.86 mg/l respectively. The LC50 values indicated that adult fish was more tolerant to copper than the juveniles. The pH level was slightly decreased with increasing concentration of copper solution. Changes in fish behaviour such as fast opercular beat, jerky movement, excessive secretion of mucus on body surface and loss of balance were observed in the experimental groups during the toxicity test